Płaszczyzny interakcji między człowiekiem a maszyną: zarys prob- lematyki z perspektywy nauki o komunikacji społecznej - Skrzypiec, Aleksandra (Człowiek i Społeczeństwo, 2025)
The dynamic technological development in the domain of Artificial Intelligence and other related disciplines, such as robotics, makes the space to phrase new research questions, which demand social communication and media science reflection. ai in the form of embodied robots, invisible social bots, voicebots, chatbots, and digital software has entered the world of social communication and became an inherent component. Contemporary, increasingly technologically advanced tools play the role of interlocutors in the communication process and in result, new dynamic forms of interactions, relations and collaboration are being created between human and machine. This theoretical article aims to present emerging – yet significant from the perspective of the science of social communication and media – research areas on contemporary machines designed to work with humans. The author concentrates on three key issues in the text: 1) cleaving of major, from a discipline point of view, terms, which have orings in engineering and technology sciences; 2) showing new interaction areas between people and machines; 3) doing synthetical overview of approaches in this topic. Therefore, the considerations undertaken represent an attempt to formulate a starting point for further analysis on the role and significance of non-human subjectivities in social communication.